Current Prescribing Practices in Bacterial Skin Infections in a Tertiary care hospital- A Prospective study - Syamala Dimma; Lakshmana Chintala; Swathi Ratnam Regidi; Sanuvada Vijay Rama Raja Sekhar (Asian Journal of Medical Sciences, 2023)
Background: Skin diseases of microbial etiology are caused by bacteria, fungi, viruses, and ectoparasites, of which bacterial infections are most common than others. Antibiotic resistance among the micro-organisms is developing due to indiscriminate use of antibiotics and irrational prescription of drugs. Aims and Objectives: The aims of this study were to assess various aspects of prescription pattern and rational use of antibiotics for bacterial infections in the department of dermatology. Materials and Methods: A prospective analysis of 120 patients attending Dermatology Out Patient Department, at Government Medical College, Srikakulam, for 16 months (June 2017–September 2018) was carried out to analyze the usage of antibiotics through various routes to treat dermatological infections. The number of antibiotics prescribed, their name, class of drug, frequency and route of administration, and duration were recorded and analyzed using descriptive statistics. Results: Among the study population, 55.9% were male and 44.1% were female. Acne vulgaris (25%) is the most common condition, for which antibiotics were prescribed followed by impetigo (16.66%). Most commonly prescribed systemic antibiotics were penicillins (51.66%) followed by macrolides (18.33%). Most commonly prescribed topical antibiotic was mupirocin (33.33%) followed by clindamycin (25%). The most preferred route of antibiotic administration was oral route (62.44%). Conclusion: Prescription pattern of antibiotics in this study proved that dermatologists followed rationality and contributed their part to curb the spread of antibiotic resistance. Periodic screening of drug prescribing pattern studies should be done to rationalize the prescription, to reduce errors, and to increase therapeutic benefits and cost-effective management.